Anatomical properties of Eucalyptus grandis wood and transition age between the juvenile and mature woods - Palermo, G. P. de M.; Latorraca, J. V. de F.; de Carvalho, A. M.; Calonego, F. W. [UNESP]; Severo, E. T D [UNESP] (Springer Nature, 2015)
The present study is aimed at evaluating the anatomical characteristics of Eucalyptus grandis wood and the transition age between the juvenile and mature woods. Four trees of 23-year-old E. grandis were used. The juvenile, transition and mature wood zones were found by fiber length measurement from the pith to the bark. Samples were taken from juvenile wood, transition wood and mature wood and the anatomical properties of the wood were determined. The results showed that: (1) the fiber length, cell wall thickness, slenderness ratio, cell wall fraction and tangential vessel diameter increase from pith to bark; (2) fibers, axial parenchyma, ray parenchyma cells and vessels are equally distributed from pith to bark; (3) the transition zone between juvenile and mature wood occurs between the age of 8 and 13 years.